2014
DOI: 10.7243/2054-9911-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Elevated body fat is a risk factor for venous thromboembolism and thrombotic complications

Abstract: Objective: The aim of the study is to analyze the relationship between body composition and BMI with venous thromboembolism (VTE) and major complications: recurrence and post-thrombotic syndrome. Patients and methods:We performed a case-control study of a group of patients with VTE (n=138) and a control group (n=127) with no history of thrombosis. BMI was calculated using the formula: BMI=weight (kg)/height 2 (m). The body composition of each subject was obtained by bioelectrical impedance analysis using the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
2
6
1
Order By: Relevance
“…The observed associations in the present study were mostly influenced by the confounding factor total body fat. This is in line with findings of other studies, in which body fat has been associated with concentrations of glucose and HbA1c, and also with VT, possibly due to an adiposity‐driven low‐grade inflammation leading to a hypercoagulable state …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The observed associations in the present study were mostly influenced by the confounding factor total body fat. This is in line with findings of other studies, in which body fat has been associated with concentrations of glucose and HbA1c, and also with VT, possibly due to an adiposity‐driven low‐grade inflammation leading to a hypercoagulable state …”
Section: Discussionsupporting
confidence: 92%
“…Model 1 (green) = crude model. Model 5 (blue) = model 1 adjusted for age, sex, % total body fat, smoking, ethnicity, education, physical activity, active cancer, menopausal status, current use of oral contraceptive pill, current use of hormonal replacement therapy, and alcohol consumption other studies, in which body fat has been associated with concentrations of glucose and HbA1c, 44 and also with VT, 45 possibly due to an adiposity-driven low-grade inflammation leading to a hypercoagulable state. 23,46 In the present study, we observed elevated FVIII, FIX, and FXI levels in hyperglycemic participants.…”
Section: Glucosementioning
confidence: 99%
“…On the other hand, there was a higher prevalence of malignancy in normal BMI patients (P < .03). The frequency of Doppler ultrasound follow-up performed in obese patients was significantly higher than that of normal weight patients, 3 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) vs. 2 (1-20); P ¼ .001.…”
Section: Normal Overweight and Obese Patientsmentioning
confidence: 90%
“…5,[9][10][11] A recent case-control study of 265 participants showed that patients with overweight or obesity had a 3-or 5-fold increased risk of developing VTE, respectively. 12 This could be explained by the fact that increased body weight poses a prothrombotic status that alters the coagulation profile and impairs fibrinolytic activity. 4,5,13 There is a rising concern regarding the rate of obesity and its associated comorbidities in the Arab Middle East region, particularly in Qatar, in which the rate of obesity has been reported to be as high as 33% with a predominance of female over male gender.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the condition of the cardiovascular system (along with the aging) contributes to its effectiveness in thermoregulation. The elevated amount of fat in the body is a risk factor for thrombosis [4,5]. Thermal imaging has been used to detect breast cancer [6,7], it has been used in intra-operative imaging [8], in ocular imaging [9] and in the screening of fever [7].…”
Section: Introductionmentioning
confidence: 99%